2009
DOI: 10.1007/s00011-009-0118-3
|View full text |Cite
|
Sign up to set email alerts
|

Geniposide inhibits interleukin-6 and interleukin-8 production in lipopolysaccharide-induced human umbilical vein endothelial cells by blocking p38 and ERK1/2 signaling pathways

Abstract: The results show that geniposide can inhibit LPS-induced IL-6 and IL-8 production in HUVECs by blocking p38 MAPK and ERK1/2 signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 36 publications
4
28
1
Order By: Relevance
“…Our results suggest that the inhibitory effect of geniposide on cell adhesion may be related to inhibition of the NF-κB signal pathway. More recently, Liu et al reported that geniposide inhibits interleukin-6 and interleukin-8 production in lipopolysaccharide-induced HUVECs by blocking p38 and ERK1/2 signaling pathways [34] . In addition to ROS and the NF-κB pathway, extracellular regulated protein kinase (ERK), C-jun N-terminal kinase (JNK) and p38, the main members of mitogen-activated protein kinase (MAPK) family, may also be involved in high glucose-induced VCAM-1 and E-selectin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that the inhibitory effect of geniposide on cell adhesion may be related to inhibition of the NF-κB signal pathway. More recently, Liu et al reported that geniposide inhibits interleukin-6 and interleukin-8 production in lipopolysaccharide-induced HUVECs by blocking p38 and ERK1/2 signaling pathways [34] . In addition to ROS and the NF-κB pathway, extracellular regulated protein kinase (ERK), C-jun N-terminal kinase (JNK) and p38, the main members of mitogen-activated protein kinase (MAPK) family, may also be involved in high glucose-induced VCAM-1 and E-selectin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Geniposide, an iridoid glucoside, is a major component ( ≥ 2%) in the fruits of G. jasminoides Ellis. Until now, pharmacological studies of geniposide have revealed key properties, including antitumor effects (Hsu et al, 1997), modulation of DNA expression (Galvez et al, 2005), treatment of pain (Gong et al, 2014), and anti-inflammatory, coloretic, and hepatoprotective effects (Chou et al, 2003;Chen et al, 2009;Liu et al, 2010;Ma et al, 2011). However, the precise mechanisms of its effects remain poorly understood.…”
Section: Metabolism and Pharmacokineticsmentioning
confidence: 99%
“…Notably, HUVECs are involved in the release of cytokines and chemokines, as well as cell migration during the inflammatory process (4,5). Increased levels of vascular cell adhesion molecule-1 (VCAM-1) and intracellular adhesion molecule-1 (ICAM-1) are early markers of endothelial activation and dysfunction in inflammatory diseases (6).…”
Section: Introductionmentioning
confidence: 99%